Effects of a simulated wolf encounter on brain and blood biomarkers of stress-related psychological disorders in beef cows with or without previous exposure to wolves. Issue 3 (1st March 2017) - Cooke, R. F.; Mehrkam, L. R.; Marques, R. S.; Lippolis, K. D.; Bohnert, D. W.
Abstract: This experiment compared mRNA expression of brain-blood biomarkers associated with stress-related psychological disorders, including post-traumatic stress disorder (PTSD), in beef cows from wolf-naïve and wolf-experienced origins that were subjected to a simulated wolf encounter. Multiparous, non-pregnant, non-lactating Angus-crossbred cows from the Eastern Oregon Agricultural Research Center (Burns, OR; CON; n = 10) and from a commercial operation near Council, ID (WLF; n = 10) were used. To date, gray wolves are not present around Burns, OR, and thus CON were naïve to wolves. Conversely, wolves are present around Council, ID, and WLF cows were selected from a herd that had experienced multiple wolf-predation episodes from 2008 to 2015. After a 60-d commingling and adaptation period, CON and WLF cows were allocated to groups A or B (d -1; 5 CON and 5 WLF cows in each group). On d 0, cows from group A were sampled for blood and immediately slaughtered, and samples were analyzed to evaluate inherent differences between CON and WLF cows. On d 1, cows from group B were exposed in pairs (1 CON and 1 WLF cow) to experimental procedures. Cows were sampled for blood, moved to 2 adjacent drylot pens (1 WLF and 1 CON cow/pen) and subjected to a simulated wolf encounter event for 20 min. The encounter consisted of (1) cotton plugs saturated with wolf urine attached to the drylot fence, (2) reproduction of wolf howls, and (3) three leashed dogs that were walked along the fence perimeter. Thereafter, another blood sample was collected and cows were slaughtered. Upon slaughter, the brain was removed and dissected for collection of the hypothalamus, and one longitudinal slice of the medial pre-frontal cortex, amygdala, and Cornu Ammonis (1 region of the hippocampus from both hemispheres). Within cows from group A, expression of c-Fos proto-oncogene in hippocampus and amygdala were greater ( P < 0.01) in WLF vs. CON cows. Within cows from group B, expression of hippocampal brain-derived neurotrophic factor mRNA and expression of c -Fos proto-oncogene mRNA in hippocampus and amygdala were less ( P ≤ 0.04) in WLF vs. CON cows. These are key biological markers known to be downregulated during stress-related psychological disorders elicited by fear, particularly PTSD. Hence, cows originated from a wolf-experienced herd presented biological evidence suggesting a psychological disorder, such as PTSD, after the simulated wolf encounter when compared with cows originated from a wolf-naïve herd.